Pengaruh Komunikasi terhadap Kinerja Karyawan di RS Mary Cileungsi Hijau - Utarindasari, Destiana; Widianingsih, Dian (https://jurnal.binamandiri.ac.id/, 2022)
As an institution with many departments, the hospital has complex services starting from patient registration when entering the ER or inpatient care. Hospitals need communication that should be maintained between departmental administrations due to frequent misinformation between departments, especially the use of BPJS as a government program. Mary Hospital suffered financial losses due to a lack of coordination of registration information related to BPJS, which was not active while patients had to be prioritized for humanitarian reasons. This study aims to analyze the effect of communication on employee performance at Mary Cileungsi Green Hospital. The results of this study indicate that there is a significant effect of effective communication on employee performance at Mary Cileungsi Hijau Hospital.